The Correlation between Estimated Glucose Disposal Rate (eGDR) and the Severity of Nonalcoholic Fatty Liver Disease (NAFLD) in Type 2 Diabetes: eGDRand the severity of NAFLD - Obeidat, Zaina; Jaber, Dunia; Alfreahat, Osama; AlKhaldi, Mohammed; Ghanem, Leen; Obeidat, Ala’eddien; Tubasi, Ahmad; Alhabahbeh, Ruba; Rayyan, Yaser; Alhawari, Hussam (Jordan Medical Journal, 2025)
Purpose: To correlate between the degree of insulin sensitivity and degree of nonalcoholic fatty liver disease (NAFLD) in type 2 Diabetes. Methods: Our study included a total of 211 patients. For each participant, we calculated the Fibrosis-4 Index (FIB-4), an indicator for assessing the presence of advanced liver fibrosis, and the NAFLD score, which assesses the extent of liver fibrosis. These scores were then correlated with the estimated Glucose Disposal Rate (eGDR), a measure used to evaluate insulin sensitivity. Results: The mean FIB-4 score was 1.22 ± 1.54, and the mean NAFLD score was -0.75 ± 1.46. Moderate to severe fibrosis was present in 2.8% of patients according to the FIB-4 score and in 10.9% according to the NAFLD score. The mean eGDR score was 4.58 ± 2.41. Spearman correlation coefficients demonstrated that eGDR was weakly but significantly correlated with the FIB-4 score (r = -0.143, p = 0.042). Additionally, eGDR showed a significant correlation with NAFLD scores (r = -0.344, p < 0.001). The FIB-4 score was also significantly correlated with NAFLD scores (r = 0.821, p < 0.001). ROC curves demonstrated that eGDR significantly predicted moderate-severe fibrosis indicated by FIB-4 (71.1%; 95% CI: 58.3%-83.8%) or NAFLD scores (73.4%; 95% CI: 63.0%-83.8%). The optimal cut-off point for eGDR to predict moderate-severe fibrosis indicated by FIB-4 was 4.07, achieving a sensitivity of 65.2% and specificity of 73.8%. For predicting moderate-severe fibrosis indicated by NAFLD scores, the optimal eGDR cut-off point was 5.34, with a sensitivity of 83.3% and specificity of 65.5%. Conclusion: Our study demonstrated a significant correlation between eGDR scores and the severity of NAFLD. Based on our findings, we suggest considering a lower cut-off point for eGDR, specifically between 4.07 to 5.34, to enhance the prediction of NAFLD in the context of insulin resistance.